Synthesis and Characterization of Complexes of Mn(II), Co(II), Ni(II) and Cu(II) with an Aroylhydrazone Ligand - MITU, L.; KRIZA, ANGELA (Asian Journal of Chemistry, 2010)
New complexes of Mn(ll), Co(II), Ni(II) and Cu(II) have been obtained with the aroylhydrazone ligand (INH2AP), formed through the condensation of isonicotinoylhydrazine with 2-aldehyde pyrrole. The complexes were characterized by elemental analysis, IR and UV-Vis, magnetic susceptibility, thermal analysis. For the complex of Cu(II) the ESR spectrum was also determined. The elemental analysis suggests a stoichiometry of 1 : 2 (metal: ligand) for the Co(II); Ni(II) and Cu(II) complexes and of 1 : 1 for the Mn(II) complex. The magnetic moments and the electronic spectra indicate an octahedral stereochemistry for all the complexes. The infrared spectra evince the fact that the ligand is coordinated to the metal ions through the atom of oxygen amide (C=O) and the azomethine nitrogen.